1993
DOI: 10.1093/nar/21.9.2087
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of LTR sequences involved in the protoplast specific expression of the tobacco Tnt1 retrotransposon

Abstract: The tobacco Tntl retrotransposon is the only plant retrotransposon that has been shown to be transcriptionally active, and its transcription is strongly induced when preparing leaf-derived protoplasts. We have analysed in this paper the LTR sequences important for Tntl expression in tobacco protoplasts. We show that LTR sequences upstream of the TATA box are sufficient to confer protoplast-dependent induction to a heterologous promoter. We also show that this region contains two short activator elements, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 33 publications
6
60
0
Order By: Relevance
“…The sequence GGCATTTGGC found from position )125 to )116 is very similar to the BI core sequence found in Tnt1 (Casacuberta and Grandbastien 1993), although the BI-like sequence is located downstream of the BII-like region instead of upstream as observed in Tnt1 (Fig. 3; Casacuberta and Grandbastien 1993). Four motifs with the sequences (T)TGAC(C) that are identical to the consensus of the elicitor-responsive elements found in the promoters of the parsley PR-1 genes (Rushton et al 1996) and the maize PRms gene (Ravento s et al 1995) were found in the distal upstream region from )683 to )426 (Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The sequence GGCATTTGGC found from position )125 to )116 is very similar to the BI core sequence found in Tnt1 (Casacuberta and Grandbastien 1993), although the BI-like sequence is located downstream of the BII-like region instead of upstream as observed in Tnt1 (Fig. 3; Casacuberta and Grandbastien 1993). Four motifs with the sequences (T)TGAC(C) that are identical to the consensus of the elicitor-responsive elements found in the promoters of the parsley PR-1 genes (Rushton et al 1996) and the maize PRms gene (Ravento s et al 1995) were found in the distal upstream region from )683 to )426 (Fig.…”
Section: Resultssupporting
confidence: 64%
“…3). The sequence GGCATTTGGC found from position )125 to )116 is very similar to the BI core sequence found in Tnt1 (Casacuberta and Grandbastien 1993), although the BI-like sequence is located downstream of the BII-like region instead of upstream as observed in Tnt1 (Fig. 3; Casacuberta and Grandbastien 1993).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Whereas the 5.3-kb RNA would correspond to the expected size of a full-length TLC1.1 transcript, the nature of the 6-kb RNA is unclear. Nevertheless, longer hybridizing transcripts have also been reported in RNA-blot analysis with the Tnt1 retrotransposon probe (Casacuberta and Grandbastien, 1993), indicating that this longer transcript might correspond to a TLC1.1-derived RNA. The effect of drought and salt stresses on TLC1.1 expression was analyzed by RT-PCR and compared with the expression of the L. chilense endochitinase and H1 histone-like genes, both reported to be induced by drought (Chen et al, 1994;Wei and O'Connell, 1996).…”
Section: Expression Analysis Of the Retrotransposon Tlc1mentioning
confidence: 98%
“…Signals controlling retrotransposon expression of these elements are located within the 5# LTR and the adjacent untranslated region. Several cis-acting elements corresponding to tandem repeated sequences and specific DNA motifs have been identified in the LTR U3 domains and have been shown to be involved in the induction of retrotransposon transcription by biotic and abiotic stress factors (Casacuberta and Grandbastien, 1993;Grandbastien et al, 1997;Vernhettes et al, 1997;Grandbastien, 1998;Takeda et al, 1998Takeda et al, , 1999. Within this region, high variability is indeed observed among the different subfamilies of plant retrotransposons, a trait that has been recently associated with the ability of these promoters to respond to different stressassociated signaling molecules (Marillonnet and Wessler, 1998;Vernhettes et al, 1998;Araujo et al, 2001).…”
mentioning
confidence: 99%